2018
DOI: 10.1159/000491671
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Three Genetic Variants in MicroRNAs (Rs11614913, Rs2910164, Rs3746444) and Prostate Cancer Risk

Abstract: Background/Aims: MicroRNAs (miRNAs) are a class of small non-coding RNA molecules which play a significant role in transcriptional and translational regulation. Published data on the association between the miRNA SNPs and prostate cancer (PCa) risk are somewhat inconclusive. Methods: We performed a meta-analysis of all available studies including 2,227 patients and 2,331 control subjects to evaluate the impact of three common genetic variants of microRNAs in prostate cancer risk. Odds ratios (ORs) with 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…All four miRNA gene variant associations noteworthy to detect an OR of 1.1 that were also noteworthy (FPRP < 0.2) were included in these 16 comparisons. The other 12 comparisons were miR‐196a2/rs11614913 T vs. C (OR, 1.21; P < .0001); miR‐27a/rs895819 GG vs. AA + AG (OR, 1.49, P < .001) and colorectal cancer ; miR‐196a2/rs11614913 C vs. T (OR, 1.40, P < .00001) and oesophageal cancer ; miR‐146a/rs2910164 G vs. C (OR, 1.15, P < .001); miR‐196a2/rs11614913 T vs. C (OR, 0.77, P < .00001) and gastric cancer ; miR‐146a/rs2910164 C vs. G (OR, 1.19, P < .001) and bladder cancer ; miR‐499/rs3746444 homozygous model (OR, 1.64, P < .001) and breast cancer ; miR‐146a/rs2910164 CC vs. GG + GC (OR, 0.52, P < .001); miR‐499/rs3746444 (OR, 2.07, P < .001) and cervical cancer ; miR‐499/rs3746444 GA vs. AA (OR, 1.60, P < .001) and prostate cancer ; miR‐146a/rs2910164 CC vs. GG (OR, 1.28, P < .001) and lung cancer ; and miR‐499/rs3746444 G vs. A (OR, 1.57, P < .001) and oral squamous cell cancer …”
Section: Resultsmentioning
confidence: 99%
“…All four miRNA gene variant associations noteworthy to detect an OR of 1.1 that were also noteworthy (FPRP < 0.2) were included in these 16 comparisons. The other 12 comparisons were miR‐196a2/rs11614913 T vs. C (OR, 1.21; P < .0001); miR‐27a/rs895819 GG vs. AA + AG (OR, 1.49, P < .001) and colorectal cancer ; miR‐196a2/rs11614913 C vs. T (OR, 1.40, P < .00001) and oesophageal cancer ; miR‐146a/rs2910164 G vs. C (OR, 1.15, P < .001); miR‐196a2/rs11614913 T vs. C (OR, 0.77, P < .00001) and gastric cancer ; miR‐146a/rs2910164 C vs. G (OR, 1.19, P < .001) and bladder cancer ; miR‐499/rs3746444 homozygous model (OR, 1.64, P < .001) and breast cancer ; miR‐146a/rs2910164 CC vs. GG + GC (OR, 0.52, P < .001); miR‐499/rs3746444 (OR, 2.07, P < .001) and cervical cancer ; miR‐499/rs3746444 GA vs. AA (OR, 1.60, P < .001) and prostate cancer ; miR‐146a/rs2910164 CC vs. GG (OR, 1.28, P < .001) and lung cancer ; and miR‐499/rs3746444 G vs. A (OR, 1.57, P < .001) and oral squamous cell cancer …”
Section: Resultsmentioning
confidence: 99%
“…However, there is disparate data concerning miR-146a polymorphisms and the susceptibility to other cancers. Hashemi et al showed no statistically signi cant association between miR-146a rs2910164 polymorphisms and prostate cancer in an Iranian population [17] despite a meta-analysis demonstrating that the rs2910164 CC genotype was associated with decreased prostate cancer risk in an Asian population [18]. In addition, whilst the miR-146a rs2910164 GC allele was signi cantly associated with breast cancer in a Pakistani population [9] this was not the case in Azeri subjects from Iran [19].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, (Ghanbari et al, 2016) identified associations of rs897984 in miR-4519 and rs11651671 in miR-548at-5p with Parkinson's disease. In addition, rs11614913 in miR-196a2, rs2910164 in miR-146a, and rs3746444 in miR-499 contributed to the risk of prostate cancer in Asian descendants (Mi et al, 2018). However, to the best of our knowledge, the associations between miRNA gene SNPs and TA susceptibility have not been explored.…”
Section: Introductionmentioning
confidence: 96%